Dynamic System Modeling of Concentrated Electrical Energy Provision with Reducing CO2 Emissions in East Nusa Tenggara - Rusman Sinaga; Frans Mangngi; Purnawarman Ginting (Universitas Negeri Malang, 2023)
Electric Power Generation (EPG) sourced from Fossil Energy (FE) has triggered an increase in CO_2 emissions in the atmosphere resulting in global warming which has a systemic impact on climate change. Whatever form of mechanism to reduce the increase in earth's temperature must be implemented. One way is to use a Solar Water Pump (SWP). This research aims to determine the use of EPG in East Nusa Tenggara (ENT) and find the amount of CO_2 emissions that can be reduced using SWP. This research uses dynamic modeling methods. The research results show that the production of electrical energy sourced from FE until 2030 is 2.270.656 MWh (87.77%), while the production of electrical energy sourced from RE is 316.441 MWh (12.23% ). EPG sourced from FE in ENT results in CO_2 emissions at 22.603.641 tons. According to survey results, conversion of FEPWP to SWP can reduce CO_2 emissions at 424.942 tons.